Implementasi Strategi Pembelajaran Afektif Melalui Pembiasaan dan Keteladan Dalam Menguatkan Karakter Religius di SDLB Negeri Jenangan Ponorogo - Siti Masithoh; Ahmad Syafii SJ; Fitri Wahyuni (BASICA, 2023)
This study aims to determine the implementation of affective learning strategies through habituation and role models and their impact on strengthening the religious character of students with special needs at SDLB Negeri Jenangan Ponorogo. Using a qualitative approach, this study explores in depth the learning process that emphasizes the affective aspect as a means of character formation. The results of the study indicate that habituation and role model strategies that are applied consistently and empathetically are able to instill religious values such as discipline in worship, honesty, politeness, and gratitude effectively in students. These findings confirm that affective learning is a relevant approach and has a positive impact on forming religious character, especially in special education environments that require more personal, contextual, and humanistic methods.